MEDIA BUKU POP-UP DALAM STUDI CARA MEMBACA DASAR UNTUK PENDIDIKAN ANAK USIA DINI (PAUD) BINA BANGSA KAMPUNG CILIMUS CISARUA BANDUNG - Rahadi, Arie Dyan; Triyadi, Agus; triadi, Agus (LPPM BSI Bandung, 2014)
Abstract - The method of education is how we convey basic information well, but what about when education becomes less precise method, for example, in early childhood education (ECD) Bina Bangsa, the method presented in the form of childrens simple printed information sheet without any variation , which make it interesting, and not appropriate for children. The method the author of this work is to design, direct observation and interviews in a study in order to obtain the required data. The author makes a work of Pop-Up book for the needs of early childhood education, which is summarized in the title of